MULHERES E SESMARIAS: A CONCESSÃO DE TERRAS E O COTIDIANO FEMININO EM MATO GROSSO (1750-1822) - Augusto, Bruno Cezar Bio (2019)
This research discusses the daily relations in Mato Grosso between the years 1750 and 1822. The temporal cut is pertinent in our research because it covers the Pombaline government, with the attempts to structure strong administrative institutions in the Portuguese domain, as well as the government of Dona Maria, with the concern of measuring the sesmarial territory, by the Alvará of 1795, of all Portuguese America. For the Mato Grosso captaincy, the second half of the eighteenth century was a time of diplomacy between the Spaniards and the Portuguese in the quest to resolve land holdings between Spain and Portugal in America. By adjusting the magnifying glass of the historian, the documentation made it possible to understand that the inhabitants of the captaincy, both men and women, used daily wiles to seek their rights in justice, whether by repossessing vacant lands, contesting testamentary inheritances, or preoccupied with their trades . The two main urbanization of the locality, Vila Bella and Villa do Cuiabá, were the stages of feminine practices visualized by us as forms of resistance of a period in which the behavior of women, both white and black, should, for the State and Church, obey some rules. We noticed, in writing the sources, that Cuiabana and Vilabelana society created some ways, such as blacks requiring letters from sesmarias, white women concerned with raising cattle, or with the support of their children and other scenarios from that period from the sources to circumvent the system metropolitan jurisdictional assuring its properties, whether of land.